ANALISIS STRATEGI GURU KELAS DALAM MENGHADAPI GAYA BELAJAR SISWA KELAS 2 DI SD NEGERI PLELEN 04 KECAMATAN GRINGSING - Faradisa, Vindy Milla; Kusumadewi, Rida Fironika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
In the context of education, it is very important for teachers to understand the different ways students receive and process information. Each learning style has a different approach, so teachers need to develop teaching strategies that can effectively reach all student learning types. This study aims to describe the strategies used by classroom teachers in dealing with three learning styles of grade 2 students at SD Negeri Plelen 04, Gringsing District. The research method used is a qualitative method with a case study approach. Data collection techniques through observation, interviews, and documentation. The results showed that the strategies used by teachers for students with visual and auditory learning styles used expository learning strategies. Meanwhile, students with kinesthetic learning styles use cooperative learning strategies and inquiry. Understanding students learning styles and applying appropriate teaching strategies are the keys to success in improving the quality of learning in the classroom.